The Verbalizers of the Toba Batak Language - Marpaung, Magdalena Br.; Indrawati, Ni Luh Ketut Mas; Suparwa, I Nyoman; Malini, Ni Luh Nyoman Seri (Randwick International of Education and Linguistics Science Journal, 2026)
Verbalizers (VBLZ) are morphemes which create verbs from other word types such as the noun, adjective, and other verb. This study traces, characterizes, and formulated the VBLZ of the Toba Batak Language (TBL). The data was the written and spoken form of the Toba language. The analysis was designed in qualitative descriptive and is ordered according to the focuses of the study of (1) lists of the VBLZ, (2) the way the VBLZ created verbs, and (3) the classification of the VBLZ. There are 3 findings in this study. Firstly, there are 5 VBLZ in the TBL; mar-, maN-, pa-, -on, and -i. The VBLZ created verbs directly and indirectly which determined the VBLZ into the first and second. Furthermore, the VBLZ are classified according to the impacts in creating verbs into primary VBLZ (the affixes of aspects of verb pa-, -on, and -i), and secondary VBLZ of mar- and maN-.